2018
DOI: 10.1038/s41598-018-31889-2
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis-related changes in phenotypical features of monocytes

Abstract: Hemodialysis (HD) patients exhibit chronic inflammation and leukocyte activation. We investigated the surface-marker profile of monocytes by flow cytometry to assess the chronic effect of uremia and the acute effect of dialysis on their phenotypical and functional features in 16 healthy controls (CON) and 15 HD patients before and after a polysulfone-based dialysis session. Median fluorescence intensities were analyzed indicating expression of CD14, CD16, integrins (CD11b, CD18), chemokine receptors (CCR2, CX3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 58 publications
2
28
0
Order By: Relevance
“…Previously we have shown that dialysis patients possess an altered distribution of peripheral blood monocytes presenting fewer classical and more intermediate and non-classical monocytes 8 . The high incidence of bacterial infection in dialysis patients is largely attributed to monocyte dysfunction 25 . This prompted us to compare the reactivity of monocytes between healthy controls (n = 34) and dialysis patients (n = 45).…”
Section: Resultsmentioning
confidence: 99%
“…Previously we have shown that dialysis patients possess an altered distribution of peripheral blood monocytes presenting fewer classical and more intermediate and non-classical monocytes 8 . The high incidence of bacterial infection in dialysis patients is largely attributed to monocyte dysfunction 25 . This prompted us to compare the reactivity of monocytes between healthy controls (n = 34) and dialysis patients (n = 45).…”
Section: Resultsmentioning
confidence: 99%
“…However, end-stage renal disease (ESRD) is associated with functional abnormalities in a variety of immune cells including dendritic cells, B and T cells, neutrophils, monocytes, and natural killer cells, which is not reversed by dialysis [16]. Dialysis itself may also affect immune function by causing dysfunction of neutrophils, monocytes, and T cells [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, in an effort to reduce the patient’s inflammatory state, ultrapure dialysates and other highly biocompatible dialysis materials have been introduced. Indeed, the currently used polysulphone-based dialysis membranes are not associated with abnormal circulating counts of classical CD14++/CD16− monocytes, pro-inflammatory intermediate CD14++/CD16+ monocytes, and non-classical CD14+/CD16++ monocytes in HD patients [191]. However, the elevated TLR2 expression and the concomitantly low CD163 expression observed in intermediate monocytes after HD [191] suggests that exposure to dialysis membranes still increases the inflammatory potential of monocytes in this population.…”
Section: The Impact Of Ckd On Macrophage Functions: Consequences Fmentioning
confidence: 99%
“…Indeed, the currently used polysulphone-based dialysis membranes are not associated with abnormal circulating counts of classical CD14++/CD16− monocytes, pro-inflammatory intermediate CD14++/CD16+ monocytes, and non-classical CD14+/CD16++ monocytes in HD patients [191]. However, the elevated TLR2 expression and the concomitantly low CD163 expression observed in intermediate monocytes after HD [191] suggests that exposure to dialysis membranes still increases the inflammatory potential of monocytes in this population. Interestingly, the number of CD14+/CD16+ pro-inflammatory monocyte count, the plasma cytokine level, and cytokine mRNA expression levels were significantly lower in patients on haemodiafiltration than in those on HD [192].…”
Section: The Impact Of Ckd On Macrophage Functions: Consequences Fmentioning
confidence: 99%